2016
DOI: 10.21037/qims.2016.08.11
|View full text |Cite
|
Sign up to set email alerts
|

Black blood T1rho MR imaging may diagnose early stage liver fibrosis: a proof-of-principle study with rat biliary duct ligation model

Abstract: Background: To explore black blood T1rho (T1ρ) liver imaging and investigate the earliest stage when biliary duct ligation (BDL) induced liver fibrosis can be diagnosed.Methods: MR was performed at 3 Tesla. A T1ρ prepared 2D fast spin echo (FSE) sequence with acquisition of four spin lock times (TSLs: 1, 10, 30, and 50 msec) and spin-lock frequency of 500 Hz was applied.Inherent black blood effect of FSE and double inversion recovery (DIR) achieved blood signal suppression, and 3 axial sections per liver were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
3
28
4
Order By: Relevance
“…The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation. 64 The Bayesian prediction provides probabilities, rather than a ‘yes/no’ decision; it also allows weighting of the different methods, such as IVIM, liver T1rho 65, 66 , and elastography 3840 readouts, therefore realizing multi-parameter diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation. 64 The Bayesian prediction provides probabilities, rather than a ‘yes/no’ decision; it also allows weighting of the different methods, such as IVIM, liver T1rho 65, 66 , and elastography 3840 readouts, therefore realizing multi-parameter diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…After the withdrawal of CCl4 stimulus, it seems Letter to the Editor How liver pathologies contribute to T1rho contrast require more careful studies that the lowering of elevated liver T1rho was faster than the resolve of fiber tissue deposition in rat liver. One note is the wide inter-subject variation of physiological T1rho, not only seen in healthy subjects (11), but also in male rats of similar age (Figure 4) (5). One potential explanation for Figure 4 is that these rats have diverse liver iron concentrations, but co-contributors of other sources are also possible and should be further investigated.…”
mentioning
confidence: 98%
“…Liver T1rho has been proposed as an imaging biomarker for liver fibrosis (1)(2)(3)(4)(5). In the recent study of Xie et al (6,7), 18 healthy subjects, 18 patients with fatty liver, and 18 patients with liver fibrosis had T1rho MR imaging performed.…”
mentioning
confidence: 99%
“…This has been indicated in the earlier animal studies [8, 9, 26]. In a recently study, Koon et al [27] reported on day-10 after biliary duct ligation all experimental animals can be separated from normal liver based on T1rho measurement, when liver histology resembled early stage fibrosis, and fibrous area counted for 0.38%±0.44% of liver parenchyma area. Liver T1rho may also be used as marker of liver function, as demonstrated by Allkemper et al [14] and Takayama et al [16].…”
Section: Discussionmentioning
confidence: 73%